Digital Governance Strategy for Social Inclusion in West Sumatra - Satria Arianto (Asian Digital Governance Problems, 2024)
Purpose: This study explores the digital governance approach for social inclusion in West Sumatra, Indonesia. Subjects and Methods: Using a complete method encompassing purposive sampling, based questionnaires, and numerous statistical analyses. Results:  Results indicate a substantial enhancement in the perceived effectiveness of digital governance strategy following implementation, suggesting a tremendous effect on governance effectiveness. Moreover, the implementation of digital governance strategies correlates with better ranges of social inclusion outcomes, highlighting the capacity of digital interventions in fostering inclusive development. Regression analyses screen the giant roles of stakeholder collaboration and organizational capability in promoting social inclusion, emphasizing the significance of multi-stakeholder engagement and institutional strengthening. Pearson correlation analyses further affirm sturdy wonderful institutions between digital governance strategy, stakeholder collaboration, organizational capability, and social inclusion outcome, underscoring their interconnectedness. Conclusions: This have a look at contributes valuable insights for policymakers, practitioners, and researchers, emphasizing evidence-based totally methods to digital governance for inclusive development.